The Influence of Family Structure on the Social Development of Children in Nigerian Families: A Management Perspective (Journal of Management and Social Sciences, 2025)
This study examines the influence of family structure on the social development of children within Nigerian families from a Management Perspective. The study's objectives are to identify the social issues arising from various family structures and to understand how family dynamics affect the social outcomes of children, which is also in line with research questions and research hypotheses. Descriptive survey research design is adopted., primary data was collected using structured questionnaires aligned with the study's objectives. The questionnaire contained closed-ended questions organized into sections addressing specific variables. Regression analysis utilizing the SPSS Package was employed for data analysis. The findings from the study reveal that family structure in Nigeria significantly influences social problems in Nigerian families (R2 = 0.234, p < 0.05). The study also reveals that family structure significantly influences the social outcome of children in Nigerian families (R2 = 0.465, p < 0.05). The study concludes that addressing social problems and social outcomes of children in Nigeria necessitates acknowledging the influence of family structure. Therefore, the study recommends that the Nigerian government should work towards improving the well-being of its citizens by mitigating the negative effects of social problems associated with family dynamics, implementing interventions to accommodate diverse family structures, and recognizing the importance of family dynamics in targeting policymakers, social workers, educators, and societal organizations.